EFFECTS OF ORGANO-MINERAL FERTILIZERS ON GROWTH AND YIELD OF FOUR UPLAND RICE CULTIVARS IN TWO LOCATIONS IN TARABA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Field experiments were conducted to evaluate the effects of different rates of organo-mineral fertilizers on the growth and yield of selected rice cultivars at two locations: the Teaching and Research Farm of Taraba State University, Jalingo, and Karim Lamido area of Taraba State, North-East Nigeria, during the 2024 cropping season. The experiment used a factorial (2×4×4) arrangement in a Randomised Complete Block Design (RCBD) with three replications. Treatments comprised four upland rice varieties (Faro 44, Faro 58, Faro 59, and local CP) and four fertilizer regimes: 20 t/ha cow dung (organic, OF), 300 kg/ha N.P.K 20:10:10 (inorganic, IF), a 50% cow dung + 50% N.P.K mixture (MX), and an unfertilized control (CT), resulting in 16 treatment combinations. Each plot measured 3 m × 1.5 m with 20 stands, and seedlings were transplanted at 30 cm × 30 cm spacing. Data were collected on tiller number, leaf area, 1000-seed weight, and grain yield. Results showed location significantly (P
Keywords: Organo-mineral fertilizers; Rice cultivars; Yield; Upland rice; Taraba State; Nigeria